Additional tests to investigate neuropathic pain. The value of electroneuromyography for neuropathic pain - Porto,Fábio Henrique de Gobbi (2016)
ABSTRACT BACKGROUND AND OBJECTIVES: Neuropathic pain is defined as pain induced by injury or disease involving the somatosensory system. Dysfunctions in anatomic regions responsible for the processing of pain may involve peripheral and central nervous system components. A careful history and clinical evaluation with special attention to neurologic propaedeutics are critical for the syndromic, anatomic and etiologic diagnosis of neuropathic pain. However, diagnosis is not always simple and often depends on additional tests. This chapter aimed at reviewing most commonly used additional tests in the clinical practice to help diagnosing neuropathic pain. CONTENTS: Electroneuromyography is primarily indicated for topographic, etiologic and prognostic diagnosis of peripheral nervous system diseases and for the differential diagnosis between neurogenic, myopathic and neuromuscular junction diseases. It gives real time information on what is going on in the nerve and the muscle, being fundamentally important for differential neuromuscular disease diagnosis. Some imaging methods, such as computerized tomography and magnetic resonance, for their spatial resolution, give details of anatomic structures. Other methods, such as positron emission tomography scan and functional magnetic resonance, in addition to anatomic details, also provide data on metabolic and functional measurements. In addition, imaging techniques such as spectroscopy and diffusion tensor magnetic resonance, allow the study of brain biochemical changes and conectivities with different temporal and spatial resolutions. Other additional tests, such as sensory quantification test and microneurography are seldom used in the clinical practice. CONCLUSION: Additional tests, together with careful history and neurological evaluation focused on neurologic propaedeutics, may provide important data for the diagnosis of neuropathic pain and are often used in the clinical practice.